2004
DOI: 10.1029/2003rs002999
|View full text |Cite
|
Sign up to set email alerts
|

Development of an antenna and multipath calibration system for Global Positioning System sites

Abstract: [1] Site-dependent errors such as antenna phase-center variations, multipath, and scattering can have a significant effect on high-precision applications of the Global Positioning System (GPS). Determination of these errors has proven to be elusive since no method has been developed to measure these effects accurately in situ. We have designed and constructed a prototype Antenna and Multipath Calibration System (AMCS) to obtain such in situ corrections. The primary components of the AMCS are a steerable parabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…As highlighted by Elósegui et al [1995], the permanent structures (e.g., pillars) to which the antennas are typically mounted become electromagnetically coupled 10.1002 to the antennas themselves. Calibration systems for recovering the comprehensive site-dependent antenna patterns (intrinsic APV plus multipath) have yielded promising results [Park et al, 2004;Wübbena et al, 2006]. These hardware systems, however, involve the use of large high-gain antennas or robots and have not yet been widely used to provide site-specific antenna calibrations, e.g., for a globally dispersed network of GPS ground stations.…”
Section: Using Terrestrial Antennas As Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…As highlighted by Elósegui et al [1995], the permanent structures (e.g., pillars) to which the antennas are typically mounted become electromagnetically coupled 10.1002 to the antennas themselves. Calibration systems for recovering the comprehensive site-dependent antenna patterns (intrinsic APV plus multipath) have yielded promising results [Park et al, 2004;Wübbena et al, 2006]. These hardware systems, however, involve the use of large high-gain antennas or robots and have not yet been widely used to provide site-specific antenna calibrations, e.g., for a globally dispersed network of GPS ground stations.…”
Section: Using Terrestrial Antennas As Referencesmentioning
confidence: 99%
“…Site-specific APV calibrations can be readily developed using empirical techniques [Hurst and Bar-Sever, 1998]. Characterizing the absolute pattern correctly, however, may first require the use of dedicated calibration systems [e.g., Park et al, 2004;Wübbena et al, 2006] at one or more reference stations in order to compensate for singularities with the network scale.…”
Section: Summary and Future Workmentioning
confidence: 99%
“…In addition, the effects of unmodelled signal from the reactive near field were studied by Dilssner et al (2008) who also found substantial time-variable noise in GPS coordinate time series. A robust method to model (e.g., Park et al 2004) or mitigate multipath and scattering effects (e.g., Elosegui et al 1995) must be a high priority in the GPS community and similar studies are required for DORIS.…”
Section: Local Site Effectsmentioning
confidence: 99%
“…An example in the former category is the so-called ''monument motion'' (discussed below), while examples for the latter include positioning errors caused by multipath (also discussed below), antenna phase center variations [Elósegui et al, 1995;Park et al, 2004], unmodeled atmospheric effects [e.g., Davis et al, 1985;Treuhaft and Lanyi, 1987;Kedar et al, 2003], and satellite orbit errors [e.g., Baueršíma, 1983]. While some of these errors (e.g., atmospheric effects and satellite orbit errors) will have some degree of cancelation over shorter intersite distances, others are noncanceling, site-specific effects (e.g., monument motion and local multipath errors).…”
Section: Introductionmentioning
confidence: 99%
“…The two stations at Slide Mountain receive signals that are split from the same antenna, thus creating a ''zero-baseline'' (ZBL) network. Since these stations have the same instrumentation as that of the short-baseline stations (Table 1), we can use them to determine lower bounds for the level of receiver or software noise we might expect [Park et al, 2004].…”
Section: Introductionmentioning
confidence: 99%